2022
DOI: 10.1108/k-05-2022-0782
|View full text |Cite
|
Sign up to set email alerts
|

Product pricing and green decision-making considering consumers' multiple preferences under chain-to-chain competition

Abstract: PurposeIt is necessary to implement green supply chains. But green development needs to be gradual and coexist with ordinary products in the market. This paper aims to study the green and ordinary product pricing and green decision-making under chain-to-chain competition.Design/methodology/approachThis paper considers consumers' multiple preferences and takes two competitive supply chains with asymmetric channels as the research object. Through the construction of the game models involving different competitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Cao et al [30] analyzed the impact of product substitution and consumer green awareness on manufacturer encroachment strategies, green innovation efforts, and supply chain performance based on the environmental attributes of the different products in the two categories. Wang et al [31] developed a two-chain model for selling heterogeneous products under an asymmetric channel structure. They found that as the degree of product substitutability increases, the green supply chain improves the greenness of the products, the retail price and demand of both products increase, and the performance of the supply chain system is improved.…”
Section: Supply Chain Considering Product Substitutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cao et al [30] analyzed the impact of product substitution and consumer green awareness on manufacturer encroachment strategies, green innovation efforts, and supply chain performance based on the environmental attributes of the different products in the two categories. Wang et al [31] developed a two-chain model for selling heterogeneous products under an asymmetric channel structure. They found that as the degree of product substitutability increases, the green supply chain improves the greenness of the products, the retail price and demand of both products increase, and the performance of the supply chain system is improved.…”
Section: Supply Chain Considering Product Substitutionmentioning
confidence: 99%
“…For example, refs. [31,39] studied the green decision problem for heterogeneous substitutes in a two-chain system with asymmetric and symmetric structures, respectively. Hong et al [41] discussed the impact of consumers' differentiated purchasing behaviors (that is, different levels of environmental awareness and reference identification) on the design of green products and the pricing strategies for substitutable products.…”
Section: Research Gapmentioning
confidence: 99%
“…Because of this, the company can put resources into other endeavours that would not have been possible without these cutting-edge methods. Hence, if the management of a firm opts to operate sustainably, the economic constraints and crises that drive them to cut costs establish the way to a brighter future [8,10,[40][41][42][43][44]. The tactic for business operations-cost minimisation-was broadened to include business strategy and industry.…”
Section: Literature Review For Gap Identificationmentioning
confidence: 99%
“…In summary, the single-item pricing optimization model can be written as. Kennedy originating from the study of birds foraging for food [9][10][11]. The PSO algorithm simulates the process of finding food in a flock of birds, where each bird in the flock is viewed as a particle of the population in the algorithm.…”
Section: Daily Replenishment and Pricing Strategy Development For Eac...mentioning
confidence: 99%